Impact of contraceptive counselling, an essential element of post-abortion care, on uptake of contraceptives: a cross-sectional study of adolescents who received post-abortion care services in Makueni County, Kenya - Ngugi, Rachel N.; Musovya, James; Njoroge, Wacuka G.; Kodhiambo, Maurice O. (International Journal Of Community Medicine And Public Health, 2021)
Background: Contraceptive counselling and provision of contraceptives are essential elements of the post-abortion care model which was first published in 1994 with an aim of promoting post-abortion care as an effective public health strategy. Despite being core elements of this model, they are often overlooked during provision of post-abortion care services as health care workers focus on emergency services and removing the retained products of conception. The aim of this study was to assess the impact of contraceptive counselling on uptake of contraceptives among adolescents presenting for post-abortion care. Methods: A cross-sectional study involving 100 adolescent girls who presented for post-abortion care at the Kibwezi-east sub-county hospital, Makueni county, Kenya. Self- administered questionnaires were used for data collection and data was analyzed using SPSS version 25. Chi-square was used to compare study participants who received/did not receive contraceptive counselling and their uptake of contraceptives. Results: The mean age of the 100 participants was 17 years (SD=1.457). 98% of them were formally educated, 57% had the mother as their only guardian and majority of them were of Christian religion (56%). 41% (n=41) received contraceptive counselling services and 59% (n=59) were not counselled. Among the 41 participants who received contraceptive counselling, 92% (n=37) of them took up a contraceptive method and 8% (n=4) did not take up any method and among the 59 participants who did not receive contraceptive counselling, 51% (n=30) of them took up a contraceptive method while 49% (n=29) did not. Conclusions: Contraceptive counselling remains an integral part of post abortion care and in this study it was found to have a positive correlation with utilization of post abortion contraceptives (rs=0.412, p=0.000).